Amorphous Molybdenum Sulfide Deposited Graphene Liquid Crystalline Fiber for Hydrogen Evolution Reaction Catalysis. (3rd February 2017) - Lee, Kyung Eun; Sasikala, Suchithra Padmajan; Lee, Ho Jin; Lee, Gil Yong; Koo, Sung Hwan; Yun, Taeyeong; Jung, Hong Ju; Kim, InHo; Kim, Sang Ouk
Abstract : Wet spinning of graphene oxide liquid crystal exploits 1D conductive catalyst support and electrochemical deposition realizes successful hybridization with amorphous molybdenum sulfide. Geometrical advantage of reduced graphene oxide (RGO) fiber can hold larger amount of amorphous molybdenum sulfide and optimized loading on RGO fiber provides high catalytic activity and stability for hydrogen evolution reaction.